Removal of Lead Ions from Wastewater by using a Local Adsorbent from Charring Tea Wastes - Abd AL-Hussain, Zahraa Kadhim (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
Adsorption of lead ions from wastewater by native agricultural waste, precisely tea waste. After the activation and carbonization of tea waste, there was a substantial improvement in surface area and other physical characteristics which include density, bulk density, and porosity. FTIR analysis indicates that the functional groups in tea waste adsorbent are aromatic and carboxylic. It can be concluded that the tea waste could be a good sorbent for the removal of Lead ions from wastewater. Different dosages of the adsorbents were used in the batch studies. A random series of experiments indicated a removal degree efficiency of lead reaching (95 %) at 5 ppm optimum concentration, with adsorbents R2 =97.75% for tea. Three models (Langmuir, Freundlich, and Temkin) have been used to show which is the best operation. It was found that tea waste has an adsorption capacity (qmax) equal to 2.7972 (mg/g). Equilibrium data fitted well with the Freundlich isotherm because Freundlich assumptions are more suitable to represent the relationship between adsorbent and adsorbate. Two Kinetic Models were applied (first order, and second order) for this study. The adsorption kinetics was investigated and the best fit was achieved by a first-order equation with R2= 95.91%.